Effects of Current Ratio, Debt-to-Equity Ratio, and Return on Equity on PT United Tractors Tbk Stock Price - Suwardi Suwardi; Mutiara Aprima Ayu; Randy Reliantama Tanamas (Jurnal Ilmiah Multidisiplin, 2026)
This study examines the effects of the Current Ratio, Debt-to-Equity Ratio, and Return on Equity on the stock price of PT United Tractors Tbk during the 2016–2023 period. The study employed a quantitative approach using secondary data obtained from the company’s quarterly financial statements and stock price records published by the Indonesia Stock Exchange and the company’s official website. Purposive sampling was applied, resulting in 32 quarterly observations. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, partial significance tests, simultaneous significance tests, and the coefficient of determination with IBM SPSS version 25. The results show that the Current Ratio has a negative and significant effect on stock price, with a significance value of 0.030. In contrast, the Debt-to-Equity Ratio and Return on Equity do not have significant partial effects, with significance values of 0.087 and 0.380, respectively. Simultaneously, the three financial ratios have a significant effect on stock price, as indicated by a significance value of 0.049. The adjusted coefficient of determination is 0.160, indicating that the model explains 16% of the variation in stock price, while the remaining 84% is associated with factors outside the model. These findings indicate that liquidity, leverage, and profitability should be considered collectively when evaluating stock price movements, although other financial and market-related factors remain dominant.